2022
DOI: 10.1111/papr.13101
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL‐10 systemic low level and highest pain score in patients during symptomatic SARS‐CoV‐2 infection

Abstract: Background Despite the wide variety of Covid‐19 symptoms, pain and the related mechanisms underlying unsettled nociceptive status are still under‐prioritized. Understanding the complex network of Covid‐19‐related pain may result in new lines of study. It is unknown whether patient's immunological background influences pain in the acute phase of Covid‐19, including musculoskeletal pain. Thus, we evaluated the blood levels of selected molecules that are upregulated in SARS‐CoV‐2 infection and analyzed a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The analgesic role of IL-10 is well-established in preclinical studies 16,29,37,38 . Moreover, in humans, higher levels of circulating IL-10 are associated with reduced pain [39][40][41][42][43] . However, a mechanistic explanation widely applicable from animal models to humans has not yet been demonstrated.…”
Section: Discussion: (1475 Words)mentioning
confidence: 99%
“…The analgesic role of IL-10 is well-established in preclinical studies 16,29,37,38 . Moreover, in humans, higher levels of circulating IL-10 are associated with reduced pain [39][40][41][42][43] . However, a mechanistic explanation widely applicable from animal models to humans has not yet been demonstrated.…”
Section: Discussion: (1475 Words)mentioning
confidence: 99%
“…The post-infection follow-up of COVID-19 survivors unveiled a range of symptoms, encompassing general pain (13.40%), joint pain (28.25%), muscle pain (13.30%), headache (9.50%), and chest pain (12.12%) [ 214 ]. Pain development is mainly associated with direct action through ACE2 receptors [ 215 ], the inflammatory cytokine storm [ 216 ], and the driving effect of prostaglandins [ 217 ]. ACE2 receptors are abundant in skeletal muscle and other organs, resulting in viral harm to the muscles, and their neurophilicity can also lead to neuronal damage, resulting in pain [ 218 ].…”
Section: Therapeutic Potential Of Naringin and Naringenin In Long Covidmentioning
confidence: 99%
“…This has been proven in a study where the expression of these pro-inflammatory mediators was found to be significantly upregulated in COVID-19 patients (McFarland et al 2021 ). Moreover in a recent clinical survey the high level of inflammatory cytokine IL-1β and low level of anti-inflammatory cytokine IL-10 in systemic circulation were found to be associated with high pain score in SARS-CoV-2 patients (Bussmann et al 2022 ). The proliferation of immune cells and increased production pro-inflammatory cytokines around the sensory neurons and dorsal root ganglion in response to SARS-CoV-2 invasion leads to nociceptor sensitization.…”
Section: Deciphering the Mechanism Of Pain Associated With Covid-19mentioning
confidence: 99%